EFEK PEMUTARAN MUSIK KLASIK INSTRUMENTAL SECARA KONTINYU TERHADAP PERTUMBUHAN DAN PRODUKSI TELUR BURUNG PUYUH UMUR O - 12 MINGGU - Rikhanah Rikhanah; Dewi Hastuti; Endah Subekti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2004)
Quail responses to voice sensitively. A noisy voice around can decrease its productivity. However, it may adapt to voice treatment continually. The other studies show that classical music has a powerful effect to man to reduce stress and tension, help to moderate blood pressure and body temperature. The aim of this research is to know the effect of instrumental classical music sound treats continually to quail on its productivity. The productivity is determined by the body weight gain and egg production. A total of 225 quails divided into five treatments were used in this research. The treatments were instrumental classical music sound playing for 6 hours, 12 hours, 18 hours, and 24 hours long every day. The control treatment was silent. The experiment designed by Completely Randomised Design method. The different means of data between each treatment were analysed by Honestly Significant Different Method. The parameters of the research were quail body weight gain and quail egg production during 12 weeks maintenance. Analysis of Varian with significant level at 5% showed there is no significant effect of instrumental classical music sound on quail body weight gain. However, instrumental classical music sound has significant effect on quail egg production. Honestly Significant Different Test result indicated that there is significant effect of playing instrumental classical music for 18 hours long every day on quail egg production